2004
DOI: 10.1128/jcm.42.2.734-740.2004
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Use of PCR Amplification and Sequencing of 16S Ribosomal DNA from Cerebrospinal Fluid for Diagnosis of Bacterial Meningitis in a Clinical Setting

Abstract: We have evaluated the use of a broad-range PCR aimed at the 16S rRNA gene in detecting bacterial meningitis in a clinical setting. To achieve a uniform DNA extraction procedure for both gram-positive and gram-negative organisms, a combination of physical disruption (bead beating) and a silica-guanidiniumthiocyanate procedure was used for nucleic acid preparation. To diminish the risk of contamination as much as possible, we chose to amplify almost the entire 16S rRNA gene. The analytical sensitivity of the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
124
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(130 citation statements)
references
References 53 publications
3
124
0
3
Order By: Relevance
“…Kiausegger et al [16], reported a sensitivity of 10 cfu of E coli per PCR for the Gram-negative-specific PCR and 10 cfu for Gram-positive-specific PCR using Staphylococcus aureus. Schuurman et al [17], had a lower detection limit of 100 and 200 for Gram positive and Gram negative organisms respectively. Our protocol had sensitivity below 10 cfu/ml, which is considered as the infection threshold in 85% cases of meningitis [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kiausegger et al [16], reported a sensitivity of 10 cfu of E coli per PCR for the Gram-negative-specific PCR and 10 cfu for Gram-positive-specific PCR using Staphylococcus aureus. Schuurman et al [17], had a lower detection limit of 100 and 200 for Gram positive and Gram negative organisms respectively. Our protocol had sensitivity below 10 cfu/ml, which is considered as the infection threshold in 85% cases of meningitis [3].…”
Section: Discussionmentioning
confidence: 99%
“…Richardson et al [18], have described a PCR assay for the diagnosis of meningococcal meningitis, which had a sensitivity of 97% as compared to a CSF culture sensitivity of 55%. Schuurman et al [17], found broad range PCR was more useful in meningitis with sensitivity of 86%, specificity of 97%, positive predictive value of 80% and negative predictive value of 98% as compared to conventional culture. Xu et al [19], recommended use of highly resolving polyacrylamide matrix for separation of amplicons and digestion fragments.…”
Section: Discussionmentioning
confidence: 99%
“…However, sequencing often revealed mixed infections, which hampered species identification for 51% of the clinical samples, although the length of the generated amplicons was chosen in accordance with the fact that the size might have an effect on contamination: most contaminating DNA derives from nonviable organisms, which could imply that bigger amplicons are less sensitive with respect to contamination than small amplicons (25). Additionally, although amplicon sizes of only 500 bp are usually sufficient for identification of a clinical isolate, longer gene sequences deliver results with greater accuracy (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, tubercle bacilli take about 6-8 weeks to grow and further in patients who have been partially treated with antibiotics before admission, the results of culture for non-TB bacterial organisms is usually negative [8]. To overcome such problems, a variety of 16S rDNA PCR assays for diagnosing BM have been developed which have consequently made a significant impact on management of meningitis [9][10][11][12][13][14]. However till date, reports of PCR assay diagnosing BM and simultaneously identifying those as TBM and BM case in one reaction are scarcely reported.…”
Section: Introductionmentioning
confidence: 99%